The effects of buoyancy on sonoluminescing bubbles - Matula, T; Bezzerides, V; Hilmo, P; Couret, L; Olson, T; Crum, L; Swalwell, J; Kuhns, D; Roy, R (Acoustical Society of America, 2000)
Sonoluminescence from a single bubble was studied under microgravity and hypergravity environments to determine how buoyancy affects the light emission. The long-term objective of these experiments is to determine if buoyancy-related instabilities play a role in limiting the parameter space of single-bubble sonoluminescence. Understanding the parameter space limitations may ultimately lead to novel approaches for enhancing the extreme conditions within the bubble. Our results reveal several buoyancy-related effects, which should be further investigated in an extended microgravity environment.